2016
DOI: 10.4025/actascitechnol.v38i2.28308
|View full text |Cite
|
Sign up to set email alerts
|

<b>Human thermal comfort and architectural volume

Abstract: It has been questioned what influence the architectural variables have on the workers' thermal comfort since the building is a barrier between both the external and internal environments. This article presents the findings of an applied research that correlated the analytical thermal comfort of workers with the architectural volume of the workspace. We used the Confortímetro Sensu ® equipment and the software Analysis CST 2.1 ® for measuring thermal variables and calculating the analytical comfort of workers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…This value does not consider the opening's ratio consisting of lattice windows and skylights which contribute to the room's ventilation significantly in the Qua'a design. It is also noticed that the mean RPH is 5.44 which is within the suitable comfort range 4-8 [6]. As for AR which expresses the degree of exposure to the sky, the mean value was 1.76.…”
Section: Case Study: Results and Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This value does not consider the opening's ratio consisting of lattice windows and skylights which contribute to the room's ventilation significantly in the Qua'a design. It is also noticed that the mean RPH is 5.44 which is within the suitable comfort range 4-8 [6]. As for AR which expresses the degree of exposure to the sky, the mean value was 1.76.…”
Section: Case Study: Results and Discussionmentioning
confidence: 68%
“…In the Vázquez-Torres and Gómez-Amador study 18 variables were added such as total surface area, room dimensions, and ceiling height [5]. To find a correlation between the volume of architecture space and workers' thermal comfort De Oliveira found from his analytical study in real work environments that there was no significant correlation between the volume of architectural spaces and workers' thermal comfort since the data support the null hypothesis [6]. In another study by Muhaisen on the effect of aspect ratio (H/W) on the thermal performance of buildings in the Mediterranean climate, it was found that "the received solar radiation is reduced by 130.2% in summer with increasing the aspect ratio from 0.5 to 4.0 at (N-S) orientation" [7].…”
Section: Introductionmentioning
confidence: 99%
“…This shows that, even though using a single-loaded-corridor design to improve the thermal comfort level in the classroom, this is not enough to achieve year-round thermal comfort in Malaysian weather. The lack of thermal comfort in the hotter months implies the lack of a comfortable temperature, deleterious effects on the occupants' health and higher energy consumption [22]. These findings were supported by the user's preferences, which showed a higher rate of satisfaction in the single-loadedcorridor classroom.…”
Section: Discussionmentioning
confidence: 74%
“…Nesse contexto, é recomendável que se incentive o uso de elementos que minimizem o ganho térmico gerado pelas fachadas envidraçadas expostas à radiação, tais como brise-soleil, marquises e varandas (MARTINEZ et al, 2009;SZOKOLAY, 2008). As características da envoltória são fatores determinantes para adequação do desempenho termoenergético na arquitetura (OLIVEIRA et al, 2016). Portanto, a eficiência de uma envoltória se baseia no quanto ela protege a edificação da ação provocada pelas trocas térmicas entre o exterior e o interior (CARLO; LAMBERTS, 2010a; 2010b).…”
Section: Introductionunclassified